2019
DOI: 10.3748/wjg.v25.i6.729
|View full text |Cite
|
Sign up to set email alerts
|

Body-mass index correlates with severity and mortality in acute pancreatitis: A meta-analysis

Abstract: BACKGROUNDObesity rates have increased sharply in recent decades. As there is a growing number of cases in which acute pancreatitis (AP) is accompanied by obesity, we found it clinically relevant to investigate how body-mass index (BMI) affects the outcome of the disease.AIMTo quantify the association between subgroups of BMI and the severity and mortality of AP.METHODSA meta-analysis was performed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) Protocols. Three databases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 30 publications
0
46
1
5
Order By: Relevance
“…demonstrated that a BMI above 25 increases the risk of SAP [17]. It was previously reported that the recurrence rate of HTG-induced pancreatitis was about 25-30%, while the rate was as high as 50% in this study [16,18].…”
Section: Discussioncontrasting
confidence: 45%
“…demonstrated that a BMI above 25 increases the risk of SAP [17]. It was previously reported that the recurrence rate of HTG-induced pancreatitis was about 25-30%, while the rate was as high as 50% in this study [16,18].…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, potential mixture of chronic pancreatitis and RAP could influence the outcome. As reported, body mass index (BMI) highly influence the outcome of AP (Dobszai et al, 2019). The lack of data on the changes in body weight or BMI is a potential negative factor to find a causal relation between AP attacks and the rising risk of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a well-established risk factor of severity and mortality in AP patients [9, 26]. In previous studies, obesity was determined as BMI > 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%